β-catenin attenuation leads to up-regulation of activating NKG2D ligands and tumor regression in BrafV600E-driven thyroid cancer cells - Zou, Minjing; Al-Yahya, Suhad; Al-Alwan, Monther; BinEssa, Huda A.; Khabar, Khalid S. A.; Almohanna, Falah; Assiri, Abdullah M.; Altaweel, Abdulmohsen; Qattan, Amal; Meyer, Brian F.; Alzahrani, Ali S.; Shi, Yufei (Frontiers in Immunology, 2023)
BRAFV600E mutations frequently occur in papillary thyroid cancer (PTC). β-catenin, encoded by CTNNB1, is a key downstream component of the canonical Wnt signaling pathway and is often overexpressed in PTC. BRAFV600E-driven PTC tumors rely on Wnt/β-catenin signaling to sustain growth and progression. In the present study, we investigated the tumorigenicity of thyroid cancer cells derived from BrafV600E PTC mice following Ctnnb1 ablation (BVE-Ctnnb1null). Remarkably, the tumorigenic potential of BVE-Ctnnb1null tumor cells was lost in nude mice. Global gene expression analysis of BVE-Ctnnb1null tumor cells showed up-regulation of NKG2D receptor activating ligands (H60a, H60b, H60c, Raet1a, Raet1b, Raet1c, Raet1d, Raet1e, and Ulbp1) and down-regulation of inhibitory MHC class I molecules H-2L and H-2K2 in BVE-Ctnnb1null tumor cells. In vitro cytotoxicity assay demonstrated that BVE-Ctnnb1wt tumor cells were resistant to NK cell-mediated cytotoxicity, whereas BVE-Ctnnb1null tumor cells were sensitive to NK cell-mediated killing. Furthermore, the overexpression of any one of these NKG2D ligands in the BVE-Ctnnb1wt cell line resulted in a significant reduction of tumor growth in nude mice. Our results indicate that active β-catenin signaling inhibits NK cell-mediated immune responses against thyroid cancer cells. Targeting the β-catenin signaling pathway may have significant therapeutic benefits for BRAF-mutant thyroid cancer by not only inhibiting tumor growth but also enhancing host immune surveillance.